(untitled) (Economic and Political Thought, 2012)
The article is aimed at presenting the topic of shale gas in Poland – benefits and threats connected with its extraction as well as opinions for and against expressed by politicians and social activists within a discussion of the topic. The method used in the article is a case study. Such a form of analysis makes it possible to show various attitudes (of national and foreign parties) regarding extraction of this gas. The aim of this case study is to show not only ideas worth implementing but also potential mistakes that must be avoided. The shale gas case study lets the author draw conclusions what the reasons and results of the process are and shows political, economic, technical and social conditions connected with shale gas. The discussion of the analyzed topic results in a short description of the course of work on shale gas extraction and an answer to the question whether it is worth extracting. The conclusions drawn after the research in the field suggest that shale gas creates an opportunity to become independent of foreign supply of energy resources.